Strukturālas izmaiņas Bosnijas un Hercogovinas augstākajā izglītībā, kontekstā ar Boloņas procesu un integrāciju Eiropas augstākās izglītības telpā - Marković, Nena (Latvijas Universitāte, 2013)
Maģistra darbs piedāvā visaptverošu analīzi par pašreizējo situāciju Bosnijas un Hercegovinas augstākās izglītības sistēmā, koncentrējoties uz Boloņas modeļa īstenošanu publiskajās universitātēs, galvenokārt Sarajevas Universitātē - lielākajā publiskajā universitātē valstī. Tā mērķis ir analizēt, cik lielā mērā ieinteresētās puses atbalsta Boloņas modeļa ieviešanu Bosnijas un Hercegovinas augstākajā izglītībā, kā arī Bosnijas un Hercegovinas augstākās izglītības integrāciju Eiropas augstākas izglītības telpā.

This paper provides a comprehensive analysis of the current situation in higher education system of Bosnia and Herzegovina focusing on the implementation of Bologna Process at the public universities, particularly in University of Sarajevo - the largest public university in Bosnia and Herzegovina. The research problem is to examine to what extent main universities’ stakeholders support the implementation of the Bologna Process and integration of Bosnia and Herzegovina into European Higher Education Area. For these purpose three types of questionnaires were designed for following target groups: students of University of Sarajevo, academic staff of University of Sarajevo and certain number companies based in Sarajevo.
Structural changes in higher education of Bosnia and Herzegovina in the context of Bologna process and integration to European Higher Education Area (EHEA)
Keywords: Ekonomika